Mainstreaming gender in the public service, developing conducive spaces - Ramparsad, Nitasha (HTS teologiese studies, 2019)
‘Looking beyond Compliance’ assesses the role of an enabling environment as a major factor in the successful mainstreaming of gender. This article analyses the important role of political will in influencing the creation of an enabling environment. The article suggests that several role-players need to possess the political will to ensure that an enabling environment is created. Notably, the actions of an individual have an impact on the institutional reforms developed and vice versa. Political will is argued as the most influential component in the development of an enabling environment and therefore creates the enabling environment through political buy-in. The argument specifically looks at the Department of Public Service and Administration located in the South African public service.